Analysis of Democratic Character, National Spirit and Love for the Homeland in Elementary School Children - Saida, Saida; Rohana, Rohana (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
The purpose of this study is to analyze the democratic character, national spirit and love for the homeland in elementary school children. The method in this study used a descriptive method with a qualitative approach. The key informants in this study were 5 teachers and respondents were 98 elementary school students from 6003 students who were obtained by the slovin formula (n=). This research was done in all elementary schools in Rantau Selatan sub-district, Labuhanbatu district, North Sumatra province. Data collection techniques used observation, interviews and questionnaires. The technique used to analyze the data was data reduction, data presentation, and drawing conclusions. The results showed that the implementation of democratic character in elementary school students in the Rantau Selatan sub-district, Labuhanbatu district had been implemented with a percentage of 85% who strongly agreed to implement deliberation before making decisions, student behavior in applying the character of the national spirit was 87% who strongly agreed to cooperate with friends without distinguishing ethnicity, ethnicity and social status, and the behavior of students who apply the character of love for the homeland as much as 93% who strongly agree to display photos of the president and vice president, state symbols, and red and white flags in their schools. Based on the results obtained, it can be concluded that the application of democratic character, the spirit of nationalism and love for the homeland in elementary school children in the South Rantau sub-district, Labuhanbatu district is still classified in the very good category.